Modelling, design and thermo-economic evaluation of an ORC-ejector trigeneration system for waste heat recovery - Braimakis, Konstantinos; Zitouni-Petrogianni, Athina; Karellas, Sotirios; Kalogirou, Soteris A. (My University, 2017)
A novel trigeneration system based on the combined operation of an Organic Rankine Cycle (ORC) and an Ejector Cooling Cycle (ECC) for industrial waste heat recovery is simulated. The influence of different operational parameters, such as working fluid selection, pressures and temperatures on the system performance is investigated. Furthermore, special focus is given on the selection and design of key equipment components, which include the heat exchangers, the expander and the ejector. Finally, a detailed techno-economic evaluation of the system for its application for waste heat utilization from an existing glass manufacturing plant is carried out. The electrical efficiency of the system was estimated equal to 5.7 %, with the COP of the trigeneration system amounting to 10.72 %. The payback period was estimated to be less than 5 years, with an internal rate of return equal to 27 %. Nevertheless, despite the attractive economic competitiveness of the system, significant operation limitations may arise due to its complexity.
Keywords: Cogeneration; Ejector Cooling Cycle; Glass industry; Organic Rankine Cycle; Trigeneration; Waste heat recovery